(untitled) (Itinera, 2025)
The notion of disinterestedness is still central to the aesthetic debate today, as it has taken on very different and even ambiguous features throughout history. By tracing the roots of this concept, my aim is to read disinterestedness in the light of a perspective that is gaining ground in contemporary aesthetics, which sees the agential dimension as central. Kant’s interpretation is of particular interest because while it retains some of the passive traits from previous formulations, presenting the aesthetic judgments as a response, at the same time introducing some initial practical aspects. The ambiguity of Kantian disinterestedness allows us to argue, drawing from a more contemporary reflection such as that of Alcaraz León (2019), for the importance of recognizing a practical dimension inherent in taste. It contends that disinterested attention, far from being detached or inert, allows for a space of novelty, openness, and aesthetic exemplarity. This reframing positions taste not as a mere passive response but as a situated, normative practice that participates in the formation of shared meaning through example rather than rule.